2007
DOI: 10.1056/nejmoa074941
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid and Clinical Fractures and Mortality after Hip Fracture

Abstract: BACKGROUND-Mortality is increased after a hip fracture, and strategies that improve outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
1,367
14
107

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,764 publications
(1,523 citation statements)
references
References 28 publications
35
1,367
14
107
Order By: Relevance
“…Although the incidence of postinfusion increases in serum creatinine was higher in the ZOL group than in the ALN group, no long-term detrimental effect on renal function was observed, a finding consistent with previous reports by Black and colleagues and Boonen and colleagues in postmenopausal women and by Lyles and colleagues in women and men after hip fracture. (12,18,19) No osteonecrosis of the jaw was observed in either treatment group, a finding confirmed by adjudication, and no cases of avascular necrosis or delayed union/nonunion of fracture were reported. The incidence of SAEs was not different in the two treatment groups.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although the incidence of postinfusion increases in serum creatinine was higher in the ZOL group than in the ALN group, no long-term detrimental effect on renal function was observed, a finding consistent with previous reports by Black and colleagues and Boonen and colleagues in postmenopausal women and by Lyles and colleagues in women and men after hip fracture. (12,18,19) No osteonecrosis of the jaw was observed in either treatment group, a finding confirmed by adjudication, and no cases of avascular necrosis or delayed union/nonunion of fracture were reported. The incidence of SAEs was not different in the two treatment groups.…”
Section: Discussionmentioning
confidence: 51%
“…bisphosphonates. (12,18) These events generally did not lead to discontinuation from the study. Overall, they were mild to moderate in severity and resolved within 3 days of study drug administration.…”
Section: Discussionmentioning
confidence: 95%
“…(2) Data from randomized controlled trials (RCTs) have showed that bisphosphonate treatment is highly effective for the secondary prevention of osteoporotic fracture, (5) including among hip fracture patients. (6) This is reflected in many clinical guidelines from around the world that recommend the use of bisphosphonate for patients having sustained a minimal trauma fracture. (7) In January 2005, the National Institute for Health and Care Excellence (NICE) in England and Wales published new guidance recommending bisphosphonate use as a first-line therapy for the secondary prevention of osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Pharmacologic treatment of individuals with a preexisting fracture can reduce further fracture (4) and mortality risk. (5) Therefore, a major priority in osteoporosis research at present is to develop prognostic models for identifying individuals who have high risk of fracture. Using established clinical risk factors, a number of prognostic models have been developed and implemented recently.…”
Section: Introductionmentioning
confidence: 99%